Indonesian Presidential Vision and Mission 2024: A Computer-Assisted Textual Analysis - Rio Satria Nugroho; Radityo Widiatmojo (University of Muhammadiyah Malang, 2024)
February 2024 is the time for presidential election cycle for Indonesia. It becomes crucial to know how they promote their future programs in their published vision and mission books. The presidential candidates are Anies Baswedan and Muhaimin Iskandar as the first candidate, Prabowo Subianto and Gibran Rakabuming Raka as the second candidate, and Ganjar Pranowo and Mahfud MD as the third candidate. Since Indonesia has been actively promoting democracy in domestic areas and for international recognition, it is essential for the presidential candidates to promote democracy in their future programs. This paper aims to discover the most frequent discussed topics and how it reflected into the most-frequent words in their vision and mission books. Thus, this paper applied a computer-assisted textual analysis by Voyant tools. Voyant tool is known as a well-established methodology from data collection to data visualization. The results show that the first candidate focuses on the aspect of fairness in democracy, the second candidate focuses on the policy aspects of economic development, and the third one focuses on a broader aspect of economic development. Furthermore, the most frequent word analysis contributes to the theoretical understanding of computer-assisted textual analysis and democratic promotion among Indonesian presidential candidates.